Review of dose–response curves for acute antimigraine drugs: triptans, 5-HT1F agonists and CGRP antagonists. (September 2015) - Hougaard, Anders; Tfelt-Hansen, Peer
<x xml:space="preserve">Abstract</x> Introduction: Dose–response curves for efficacy and tolerability are the important determinants for the choice of doses of acute migraine drugs. Areas covered: Dose–response curves for the efficacy of seven triptans (5-HT1B/1D receptor agonists), a 5-HT1F receptor agonist (lasmiditan) and four oral calcitonin-gene related peptide receptor antagonists (telcagepant, MK-3207, BI 44370 TA and BMS-927711) in placebo-controlled trials were reviewed. In addition, dose–response curves for adverse events (AEs) were reviewed. Expert opinion: For most triptans, the dose–response curve for efficacy is flat, whereas AEs often increase with increasing doses. The two other groups of drugs also have flat dose–response curves for efficacy. Overall, the triptans still have the most favorable efficacy-tolerability profile. Current acute antimigraine drugs do not fulfill the expectations of the patients, and thus, there are many unmet needs. Although upcoming drugs may not be superior to triptans, migraine patients will potentially benefit greatly from these, especially patients who are triptan non-responders and patients with cardiovascular disease.